Effects of rainfall runoff on photothermal environment in a large and deep drinking water reservoir - Li, Cunli; Zhu, Guangwei; You, Aiju; Zhu, Mengyuan (Journal of hydrology. Regional studies, 2025)
The Lake Qiandaohu basin, China. The photothermal environment is crucial for water ecological processes in deep reservoirs, ‌as it is affected by hydrometeorological catchment processes. However, our knowledge remains limited regarding the response of the photothermal environment to different rainfall runoff intensities and changing hydrological processes due to the randomness of hydrometeorological processes. To address this, we collected photothermal environment data from three representative zones of Lake Qiandaohu between 2018 and 2019, analyzing the mechanisms by which rainfall runoff modulates this environment. The impact of rainfall runoff on the photothermal environment was influenced by the rainfall intensity and topographic location. Water column mixing occurred in the riverine zone when reservoir inflow exceeded 500 m3/s. As rainfall runoff intensity increased, the intrusion of interflow after extreme rainfall events increased the mid-layer water temperature in the transitional zone, forming a double thermocline structure. Moderate, strong, and extreme rainfall runoff substantially reduced the euphotic depth in the riverine zone by increasing the concentrations of optically active substance. The total suspended solids and chlorophyll-a were the primary factors influencing euphotic depth reductions in riverine and transitional zones, respectively (R²=0.64 and 0.45). Rainfall runoff primarily influenced the underwater photothermal environment through pulsed disturbances of the vertical temperature distribution and elevating the concentrations of optically active substances. The effects of rainfall runoff on the photothermal environment should be quantified to ensure the safety of drinking water in reservoirs. [Display omitted] •Making up for the spatio-temporal limitations of traditional monitoring of capturing unpredictable hydrological events.•Quantifying the impact of rainfall runoff on the photothermal environmental of Lake Qiandaohu.•Revealing the impact mechanism of rainfall runoff on the photothermal environment.